1999
DOI: 10.1054/jhsb.1998.0212
|View full text |Cite
|
Sign up to set email alerts
|

The Aetiology of Acute Rupture of Flexor Tendon Repairs in Zones 1 and 2 of the Fingers During Early Mobilization

Abstract: Five hundred and eight patients with 840 acute complete flexor tendon injuries in 605 fingers in zones 1 and 2 underwent surgery and postoperative mobilization in a controlled or early active motion (active flexion-active extension) regimen over a period of 7.5 years. Sixty-eight patients with 79 finger flexor divisions who did not complete the rehabilitation programme were excluded. Of the 440 patients with 728 complete tendon divisions in 526 fingers included in the study, 23 patients ruptured 28 tendon repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
94
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(103 citation statements)
references
References 44 publications
5
94
2
2
Order By: Relevance
“…These actions impose a sudden increase in the force transmitted through the repaired tendons and may subject tendons to a higher risk for ruptures. (5) Misuse of the fingers: analysis of the causes of ruptures in previous reports indicates that in approximately half of patients with ruptures, the rupture followed an ill-advised action [19,27]. Misuse of the repaired fingers, such as using the hand to lift a heavy object, may exceed the repair strength of the tendon and cause rupture.…”
Section: Repair Rupturementioning
confidence: 99%
See 1 more Smart Citation
“…These actions impose a sudden increase in the force transmitted through the repaired tendons and may subject tendons to a higher risk for ruptures. (5) Misuse of the fingers: analysis of the causes of ruptures in previous reports indicates that in approximately half of patients with ruptures, the rupture followed an ill-advised action [19,27]. Misuse of the repaired fingers, such as using the hand to lift a heavy object, may exceed the repair strength of the tendon and cause rupture.…”
Section: Repair Rupturementioning
confidence: 99%
“…Overall results by Strickland and Glogovac criteria were 92% excellent or good, 7% fair, and 1% poor. There were 43 complications in 31 patients, including five zone II ruptures (5.7%) and one rupture in zone V. Harris et al [27] reviewed results of 440 patients with 728 primary zone I and zone II flexor tendon repairs in 526 fingers. Overall, 23 patients ruptured 28 tendon repairs.…”
mentioning
confidence: 99%
“…[4] However, early active mobilization protocols may increase the repair site elongation and rupture rates. [39,40] In order to solve these problems, many multi-strand tendon suture techniques have been described. [41,42] Experimental studies have shown that suture strength and resistance to repair site gap formation increase with the number of suture strands crossing the tendon repair site.…”
Section: Discussionmentioning
confidence: 99%
“…The general rupture rate after primary repair is considered to be between 4-10% of the fingers [20,28,31]. Talking only about primary flexor tendons in zone II and repaired with the Kessler and circumferential suture, most series report a rupture rate of between 3-9% [2,3,7,[9][10][11][12]15]. In only one series of 95 children, O'Connell et al [24] report a rupture rate of 0%.…”
Section: Discussionmentioning
confidence: 99%